Visual and Refractive Outcomes Following Exchange of an Opacified Multifocal Intraocular Lens - Stewart SA; McNeely RN; Chan WC; Moore JE (Clinical Ophthalmology, 2022)
Stephen A Stewart,1,2 Richard N McNeely,1 Wing C Chan,1 Jonathan E Moore1,3,4 1Cathedral Eye Clinic, Belfast, Northern Ireland, UK; 2School of Medicine, Dentistry and Biomedical Sciences, Queen’s University Belfast, Belfast, Northern Ireland, UK; 3Biomedical Sciences Research Institute, University of Ulster, Coleraine, Northern Ireland, UK; 4Department of Ophthalmology, Tianjin Medical University, Tianjin, People’s Republic of ChinaCorrespondence: Stephen A Stewart, Cathedral Eye Clinic, Belfast, Northern Ireland, UK, Tel +44 28 9032 2020, Email stephen.stewart@doctors.org.ukPurpose: To assess the visual and refractive outcomes following exchange of an opacified multifocal intraocular lens (IOL).Patients and Methods: A consecutive series of 37 eyes (31 patients) that underwent IOL exchange between November 2015 and May 2021 were included in this study. The indication for surgery in all cases was opacification of a multifocal IOL. Outcome measures included design and anatomical location of the secondary IOL, intraoperative and postoperative complications, visual acuity and refractive accuracy.Results: An opacified Lentis Mplus multifocal IOL was explanted from all eyes and replaced with a monofocal IOL in 21 eyes (57%) and multifocal IOL in 16 eyes (43%). Secondary IOLs were implanted in the capsular bag or sulcus or were iris-fixated. IOL exchange was performed at a mean interval of 7 years after the primary surgery. Anterior vitrectomy was required for vitreous prolapse in 9 eyes (24%). Mean corrected distance visual acuity (CDVA) postoperatively was − 0.02 ± 0.08 logMAR for eyes with a monofocal secondary IOL and 0.02 ± 0.08 logMAR for eyes with a multifocal secondary IOL. Mean refractive prediction error was − 0.57 ± 0.67 D in the multifocal-monofocal group and − 0.33 ± 0.59 D in the multifocal–multifocal group.Conclusion: An opacified multifocal IOL can be exchanged for a monofocal or multifocal IOL, depending on available capsular support and the patient’s desired refractive outcome. Vitreous prolapse requiring anterior vitrectomy is the most common intraoperative complication. An improvement in visual acuity and a low postoperative complication rate were achieved in this cohort of patients.Keywords: cataract surgery, multifocal IOL, opacified IOL, IOL exchange